Multicentre evaluation of the Roche Elecsys® Active B12 (holotranscobalamin) electro-chemiluminescence immunoassay. (November 2019) - Heil, Sandra G; Bodenburg, Petra; Findeisen, Peter; Luebcke, Silke; Sun, Yuli; de Rijke, Yolanda B
Background: Vitamin B12 deficiency is a common disorder. In circulation, vitamin B12 is bound to transcobalamin (holotranscobalamin), which is considered the active form of cobalamin. The objective of this study was to evaluate the analytical performance of the Roche Elecsys Active B12 immunoassay. Methods: Limit of quantification and linearity were assessed according to CLSI EP17-A2 and EP-6A guidelines. Precision and bias of Roche Active B12 test against Architect ci8200 (Abbott) were performed according to CLSI EP-5 A3 guideline at three European laboratories. Precision requirements were set at <4% for within-run precision and <15% for intermediate precision. Requirements for method comparison were set at a slope of 1.00 ± 20%. In addition, 95% reference interval was conducted in European adults according to CLSI-EP28 guideline. Results: The assay was shown to be linear and precise and met the requirements. Lot-to-lot variation and lab-to-lab variation both were ≤4%. Method comparison with Abbott Architect showed a significant bias of 9 pmol/L, which increases to up to 23 pmol/L around the current medical decision point. The 95% reference interval of the Roche Elecsys Active B12 test was determined at 37–188 pmol/L. Conclusion: Although Roche Elecsys Active B12 immunoassay met the requirements, this test has a positive bias of 9 pmol/L, which led to an increase in lower limit of reference interval compared with Abbott test. This test first needs to be clinically validated before it can be applied as a first-line screening test in the diagnosis of vitamin B12 deficiency.